Operative service delivery planning and scheduling in Product-Service Systems - Enes Alp; Fabiana Pirola; Roberto Sala; Giuditta Pezzotta; Bernd Kuhlenkötter (Service Business, 2024)
Abstract To navigate competition and create higher value for customers, manufacturing companies are more and more adopting the strategy of Servitization by enriching their product offering with services in solutions known as Product-Service Systems (PSS). While the provision of PSS presents numerous advantages for customers and providers, they also pose significant challenges, particularly in the operative service delivery planning and scheduling. This study aims to identify decision-support within this context by conducting a systematic literature review. The analysis uncovers limitations in existing approaches and underscores unaddressed research gaps emphasizing the need for further development of decision-support systems for PSS operation.
Keywords: 330; Product-Service Systems; Operative service delivery planning; Scheduling